2009
DOI: 10.1308/003588409x432176
|View full text |Cite
|
Sign up to set email alerts
|

Early and long-term outcomes of patients undergoing liver resection and diaphragm excision for advanced colorectal liver metastases

Abstract: Liver resection and simultaneous diaphragm excision have a greater incidence of peri-operative morbidity and mortality and a significantly worse long-term outcome compared with liver resection alone. However, these data suggest that liver resection in the presence of diaphragm invasion may still offer a favourable outcome compared with chemotherapy treatment alone. Therefore, we believe that diaphragm involvement by tumour should not be a contra-indication to hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Previous studies suggested that concomitant diaphragmatic resection increases the incidence of postoperative pulmonary complications, including pleural effusion and respiratory infection. 2, 17, 18 These findings are consistent with the results in this study. The current study also found that the patients with diaphragmatic resection were more likely to have liver-related complication and overall major complications.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies suggested that concomitant diaphragmatic resection increases the incidence of postoperative pulmonary complications, including pleural effusion and respiratory infection. 2, 17, 18 These findings are consistent with the results in this study. The current study also found that the patients with diaphragmatic resection were more likely to have liver-related complication and overall major complications.…”
Section: Discussionsupporting
confidence: 93%
“…While complication rates were higher, postoperative mortality was similar between the patients with and without diaphragmatic resection in this study consistent with previous studies. 2, 3, 14, 15, 1719 Because en bloc diaphragmatic resection for the patients with pathological diaphragmatic invasion produced a better 5-year survival rate, 32%, than the rate in patients with CRLM who underwent concomitant resection of extrahepatic metastases (26–28%), 2023 en bloc diaphragmatic resection should be considered an important and possibly curative treatment approach and therefore justify the increased postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that liver resections combined with diaphragm excision resulted in high morbidity. 27,28 Otherwise, hepatectomy combined with IVC resection remains a challenging procedure due to the high risk of mortality. 12,29 In our study, we performed a subgroup risk analysis for specific organs resected and no association with increased mortality or morbidity was fond, even for IVC resections.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of Multivisceral Liver Resection (MLR) on patients with CLRM who underwent surgical treatment is unclear. Some studies have shown a negative impact of multi-visceral resections on perioperative morbidity and significantly worse long-term outcomes, 18 19 while other studies have failed to detect any difference comparing MLR and standard hepatectomy. 17 20 Despite the increased performance, the available evidence that supports MLR in patients with CRLM is from retrospective cohorts 19 20 and comparative studies with underpowered small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“… 17 20 Despite the increased performance, the available evidence that supports MLR in patients with CRLM is from retrospective cohorts 19 20 and comparative studies with underpowered small sample sizes. 17 , 18 , 19 , 20 To date, no systematic review or meta-analysis has been published on this topic, indicating that quality data supporting the indications, feasibility, and oncological outcomes of MLR are lacking.…”
Section: Introductionmentioning
confidence: 99%